1999
DOI: 10.1177/107179199900600304
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in the Making: A Comprehensive Examination of the Impact of Leadership Development Programs on Students

Abstract: Executive SummaryThis paper describes "action research" strategies that were employed to assess the process and outcomes of leadership development programs for college students. These methodologies provided evidence that formal leadership development and education programs work on college campuses and that leadership can be taught. Successful outcomes for student participants, their institutions, and their communities were documented. The action research strategy involved multiple stakeholders and assisted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 10 publications
2
66
1
1
Order By: Relevance
“…Nonetheless, researchers have attempted to understand the influence of leadership characteristics on outcomes, usually through meta-analytic techniques (see Burke & Day, 1986;Collins & Horton, 2004;Marzano, Waters & McNulty, 2005). Some investigators have studied leaders and general leadership development strategies (Brungardt, 1996;Day, 2001;Rohs, 2002;Rohs & Langone, 1997), whereas others have focused on specific topics such as student development (Zimmerman-Oster & Burkhardt, 1999) and philanthropic organizations (Russon & Reinelt, 2004). However, Yukl (2002) posited that the challenge of evaluating leadership remains.…”
Section: Evaluating a Nontraditional Leadership Programmentioning
confidence: 96%
“…Nonetheless, researchers have attempted to understand the influence of leadership characteristics on outcomes, usually through meta-analytic techniques (see Burke & Day, 1986;Collins & Horton, 2004;Marzano, Waters & McNulty, 2005). Some investigators have studied leaders and general leadership development strategies (Brungardt, 1996;Day, 2001;Rohs, 2002;Rohs & Langone, 1997), whereas others have focused on specific topics such as student development (Zimmerman-Oster & Burkhardt, 1999) and philanthropic organizations (Russon & Reinelt, 2004). However, Yukl (2002) posited that the challenge of evaluating leadership remains.…”
Section: Evaluating a Nontraditional Leadership Programmentioning
confidence: 96%
“…Third, scientific research within the leadership discipline has shifted the prevailing view away from the notion that leadership is an innate characteristic that an individual either has or does not have and toward the view that leadership can be taught and developed within anyone (Hashem, 1997;Reisberg, 1998;Zimmerman-Oster & Burkhardt, 1999). Fourth, increased reliance on cross-functional teams in the workplace (Clark, Amundson, & Candy, 2002;Dominick, Reilly, & McGourty, 1997;Esquivel & Kleiner, 1996;Housel, 2002) has led to increased demand from employers for graduates who are able to apply informal leadership skills to help manage these diverse work groups (Hackman, Olive, & Guzman, 1999).…”
mentioning
confidence: 99%
“…Indeed, there is ample evidence to suggest that leadership programs do lead to a number of positive outcomes for their participants (Cress et al, 2001;Zimmerman-Oster & Burkhardt, 1999). However, merely offering a leadership program does not guarantee a university that its students will choose to participate.…”
mentioning
confidence: 99%
“…They also found that student leaders in campus were more comfortable in communication and relationships with the higher authorities at the faculty and university (Hamid & Krauss, 2010). Zimmerman-Oster and Burkhardt (1999) found that student leaders or students who have had leadership experience tended to appreciate the depth and extent of building networks of alliances. Debnath, Tandon and Pointer (2007) found out that those individuals having leadership skills and are motivated as leaders tend to look for more complex job characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Astin's (1993) model of inputs-environments-outcomes posits that institutional practices and environmental experiences have impact on students' outcomes. Through interaction with faculty members, undergraduates learn to assess personalities and life values and choose their role models (Gilbert, 1985); through engagement with tasks they develop broader perspectives of issues and competencies (Kempster & Cope, 2010;Plumly et al, 2008); through student participation and empowerment they learn about the values and causes they would like to continue to uphold and invest in their time and energy (Komives, Lucas, & McMahon, 2007;Plumly et al, 2008), and through peer interaction they discover interpersonal skills in the midst of diversity (Gurin, Nagda, & Lopez, 2004;Hurtado, 2001;Laird, 2005)and the value of networking and shared goals (Zimmerman-Oster & Burkhardt, 1999). One of the fundamental experience these youths undergo is leadership be it leadership of self, of others, or through others.…”
Section: Introductionmentioning
confidence: 99%